MAGINARY OR EXPRESSIVE: XXI CENTURY ARCHITECTURE IN THE WORKS OF EXCELLENT MASTERS: Array - Kreizer, I. (Municipal economy of cities. Series: «Economy science», 2022)
The article deals with the theme of the interaction of "expressiveness" and "pictoriality" in the work of the masters of architecture of the XXI century. Architects' methods of work with such concepts as "imagery" and "expressiveness" became the cornerstone in understanding the concept of "modern" in the late nineteenth and early twentieth centuries. The architecture of the twentieth century in the leading countries of Europe, the USA, then the USSR, trying to keep pace with scientific discoveries and technical capabilities, created a number of rationalist avant-garde trends, which later merged into modernism (international style), gradually abandoning decor and imagery in buildings. The architects of the late 19th and early 20th centuries urged to look for means of forming a new architecture without decor and ornaments. The architecture of rationalism, and then modernism, abandoned figurativeness in an effort to express the content of modernity. This approach has led to both practical and theoretical problems. Architecture as an art form began to “speak” with the user in a different language, instead of historically proven decorative and pictorial techniques, its language became an expression of abstract forms and dynamic solutions. Looking at the works of outstanding contemporary masters, the question arises what means and techniques they use in the process of creating architectural objects and whether there is a place for decor in their work. Whether decor in the architecture of the 21st century has lost its function as an informative and visual means, whether it has become an expressive component of the architectural form is a question that will be considered in the article using the examples of famous world-class architects, and the works of Ukrainian architects will also be involved. The article also discusses modern methods of work of architects with the form.